Profile of Atherogenic Index in Elderly Individuals in Bitoa Village, Manggala District - Vera Kristianti Woso; Mutmainnah Abbas; Thaslifa Thaslifa; Rosdiana Mus (Poltekkes Kemenkes Kupang, 2025)
The atherogenic index is a good test used to measure the level of atherogenicity associated with the risk of atherosclerosis. The atherogenic index is the logarithmic ratio of TG/HDL. Atherogenic index examination in the elderly is done to see their health status. Elderly is someone who has reached the age of more than 60 years and has experienced several changes in physiological functions that will have an impact physical and psychological conditions, including stress and emotions. The purpose of this study was to describe the profile of the atherogenic index in elderly individuals. This type of research is descriptive study with a cross-sectional approach. The amount of data used in this study were 36 subjects obtained using the purposive sampling method. The results of the study at the age of 60–64 who had the resuts of the atherogenic index in the low category there were 6 respondents and the results of the atherogenic index in the moderate category there were 8 respondents, while for atherogenic index in the high category there were 16 respondents. Ages 65–69 obtained an atherogenic index in the low category, with one respondent in the high category, comprising 5 respondents. The conclusion of this study is that the atherogenic index value at the age of 60–69 obtained an atherogenic index in the low category; there were as many as 21 respondents, and the results of the atherogenic index in the moderate category were 8 respondents, while for the atherogenic index in the high category, there were 21 respondents.